The cutting time with abrasive discs can be reduced by the control of the cutting speed - Bianchi, Eduardo Carlos [UNESP]; Yokoyama, Emerson Miranda [UNESP]; Fernandes, Odilson Coimbra [UNESP]; Valarelli, Ivan de Domenico [UNESP]; Aguiar, Paulo Roberto de [UNESP] (My University, 1997)
This paper presents an experimental study on the life of abrasive discs in cut-off type operations with two conditions of cutting speed. The cutting time is shown with a comparative analysis of the cutting speed.
Keywords: Abrasive Disc; Cut-Off; Cutting Speed; Cutting Time